Decomposing differences in labour force status between Indigenous and non-Indigenous Australians - Guyonne Kalb; Trinh Le; Boyd H. Hunter; Felix Leung (Institute for the Study of Labor (IZA), 2012)
Despite several policy efforts to promote economic participation by Indigenous Australians, they continue to have low participation rates compared to non-Indigenous Australians. This study decomposes the gap in labour market attachment between Indigenous and non- Indigenous Australians in non-remote areas, combining two separate data sources in a novel way to obtain access to richer information than was previously possible. It shows that among women at least two thirds of the gap can be attributed to differences in the observed characteristics between the two populations. For men, the differences in observed characteristics of the two populations can account for 36 to 47 percent of the gap. A detailed decomposition shows that lower education, worse health, and larger families (particularly for women) explain the lower labour market attachment of Indigenous Australians to a substantial extent. Compared with previous studies, this study is able to explain a larger proportion of the gap in employment between Indigenous and non-Indigenous people due to being able to include a larger set of explanatory variables.
Keywords: J15; J21; 330; labour market attachment; Indigenous Australians; non-linear decomposition